The role of Hsp90 in the Wnt pathway of MCF7 breast cancer cells - Cooper, Leanne Claire (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 2011)
Breast cancer is one of the most common forms of cancer in not only South African women, but women all over the world. The molecular chaperone heat shock protein 90 (HSP90) is upregulated in cancer and is almost exclusively associated with proteins involved in intracellular signal transduction, thus it plays an important role in signalling pathways within the cell. In cancer, there is an aberrant activation of the Wnt signaling pathway, which results in stabilized Î²-catenin being able to translocate to the nucleus where it can trigger the transcription of oncogenes found to be involved in the self-renewal of cells. The level of Î²-catenin is usually kept in check by a destruction complex comprising glycogen synthase kinase 3-beta (GSK-3Î²), axin1, adenomatous polyposis coli (APC) which phosphorylate Î²-catenin, resulting in its ubiquitination and degradation. HSP90 has been found to be associated with GSK-3Î², but whether this association is only transient is debatable. Very little is known about the association of HSP90 with other members of the Wnt pathway in breast cancer. In this study, we have attempted to further identify the direct associations between HSP90 and GSK-3Î², Î²-catenin, p-Î²-catenin and axin1. Immunofluorescence and confocal microscopy co-localization studies suggested a potential association between HSP90 and these proteins. Treatment with HSP90 inhibitors, 17-AAG and novobiocin resulted in a shift of axin1 to what appeared to be the plasma membrane. The associations of HSP90 with GSK-3Î², Î²-catenin, p-Î²-catenin and axin1 were confirmed biochemically by co-immunoprecipitation and inhibition using 17-AAG, geldanamycin and novobiocin. We showed, for the first time that HSP90 is associated in a possible complex with Î²-catenin, p-Î²-catenin and axin1 therefore is potentially involved in the modulation of p-Î²-catenin in the Wnt pathway through the stabilization of the destruction complex.
Keywords: Cancer -- Treatment; Heat shock proteins; Cancer cells; Molecular chaperones